Suatu Studi Penggunaan Motor Induksi sebagai Generator: Penentuan Nilai Kapasitor Untuk Penyedia Daya Reaktip - Irianto, Chaerul Gagarin (Jurnal Teknik Elektro, 2004)
A squirrel cage induction motors are frequently used due to its merits such as strong andrigid construction, easy maintenance, low cost, and easy to get from the market. For everyconservation, induction motor is frequently used as a generator for the above reasons. Theoperation of motor as an induction generator needs reactive power. Reactive power can beobtained from the grid. If the induction generator separated or isolated from the grid,reactive power can be obtained from capacitor. Capacitor can be installed at the inductionmotor terminals. The capacitor value will determine the generator load. If the load isincreasing, the voltage will drop. From the experiment, we can determine the suitablecapacitor value for the load capacity provided by the induction generator.Keywords: energy conservation, reactive power, suitable capacitor value